Reliability of a test to evaluate the institutional identity of students entering the Faculty of Educational Sciences of the Daniel Alcides Carrión National University, Pasco (GnosisWisdom, 2024)
University identity is a multifaceted construct that reflects the mission and vision of an educational institution, shaped by its geographic, legal, and social context, and enriched by its philosophy, history, traditions, and symbols. This “seal of identity” fosters a sense of belonging and commitment among faculty and students. According to Pierre Bourdieu, “rites of institution” are essential to connect members to the university, establishing a “duty to be” that shapes their identity and responsibilities.University identity implies not only belonging, but also knowledge and participation consistent with the institution's mission and values, integrating and regulating its members within a psychological, historical, and cultural framework
Keywords: Test reliability; institutional identity; students